Answer:
[tex]y = \frac{1}{4}x -2[/tex]
Step-by-step explanation:
Step 1: Find the standard form of the equation
The equation that was given made no sense so I will recreate the entire equation using the point slope formula.
Use the point slope formula
[tex]y - y_{1} = m(x - x_{1})[/tex]
[tex]y - (-3) = m(x - (-4))[/tex]
[tex]y +3 = m(x + 4)[/tex]
Find the slope
[tex]m = \frac{y_{2}-y_{1}}{x_{2}-x_{1}}[/tex]
[tex]m = \frac{1-(-3)}{12-(-4)}[/tex]
[tex]m = \frac{1+3}{12+4}[/tex]
[tex]m = \frac{4}{16}[/tex]
[tex]m=\frac{1}{4}[/tex]
Combine them together
[tex]y +3 = \frac{1}{4}(x + 4)[/tex]
Convert to standard form
[tex]y +3 = \frac{1}{4}x + 1[/tex]
[tex]y +3 - 3 = \frac{1}{4}x + 1 - 3[/tex]
[tex]y = \frac{1}{4}x -2[/tex]
Answer: [tex]y = \frac{1}{4}x -2[/tex]